2015
DOI: 10.1186/s12889-015-2444-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in persons living with HIV in Burkina Faso: a follow-up over 12 months

Abstract: BackgroundIn Burkina Faso, very little is known about the quality of life of persons living with HIV through their routine follow- up. This study aimed to assess the quality of life of persons living with HIV, and its change over a 1-year period.MethodsFour hundred and twenty four (424) persons living with HIV were monitored during twelve (12) months from September 2012 to September 2013 in Ouagadougou, the capital city of Burkina Faso. Three interviews were conducted in order to assess the quality of life of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
(27 reference statements)
1
15
1
4
Order By: Relevance
“…To assess QOL, we used the specific instrument developed by WHO, the WHOQOL-HIV BREF [ 2 ] which includes 31 items. This instrument, used in other studies in West Africa [ 8 , 11 ], produces six domain scores: physical, psychological, level of independence, social relationships, environment and spirituality/religion/personal beliefs. All domain scores ranged from 4 to 20.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess QOL, we used the specific instrument developed by WHO, the WHOQOL-HIV BREF [ 2 ] which includes 31 items. This instrument, used in other studies in West Africa [ 8 , 11 ], produces six domain scores: physical, psychological, level of independence, social relationships, environment and spirituality/religion/personal beliefs. All domain scores ranged from 4 to 20.…”
Section: Main Textmentioning
confidence: 99%
“…We found in our study that, HIV-positive patients who were on ART reported better global QOL, whatever the duration of the ART. The effect of the ART on the health of PLWHA and their well-being is well documented in low-income countries [ 4 , 11 , 12 ]. The effect of ART is expressed in PLWHA by the suppression of the HIV replication, and subsequently AIDS-related mortality, morbidity and symptoms are reduced in these patients [ 12 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…For the individuals who took the serological test and had a positive result in the investigation, these serological results were not clear while filling out the questionnaires. Previous studies [26][27][28][29] paid much attention to the quality of life among people living with HIV (PLHIV). The frequency of major depressive disorder was nearly two times higher among HIV-positive subjects than among HIV-negative comparison subjects [30].…”
Section: Discussionmentioning
confidence: 99%
“…According to occupational status in the current study, 36% of HIV patients were housewives and 26% were drivers by profession. Similarly, Bakiono et al in a study reported that 23.6% were housewives and 50% were traders 11. Whereas Munsawaengsub et al reported that 57.2% patients were labourer and 7.3% remained unemployed 12.…”
mentioning
confidence: 90%